Organic matter composition in the sediment of three Brazilian coastal lagoons: district of Macaé, Rio de Janeiro (Brazil) - Zink,Klaus-Gerhard (2004)
Freshwater lagoons comprise important coastal ecosystems and natural buffers between urbanized land areas and open ocean in the Rio de Janeiro State, Brazil. Studies of sediment and water chemistry, zooplankton and bacterial communities to assess the extent of anthropogenic disturbance are available. Here we contribute with an organic-geochemical approach supplemented by some microbiological aspects to complete the characterization of these lagoonal ecosystems. Bulk organic matter and extractable lipids (aliphatic hydrocarbons, alcohols and fatty acids, sterols) were investigated from two locations per lagoon: at the seaward site and landward ends - and at two depth intervals (0-3 and 3-6 cm) per site. Urbanized Imboacica Lagoon received increased anthropogenic input over the most recent years represented by the topmost 3 cm of sediment, whereas deeper sediment layers are less affected by human influence. Eutrophication or nutrient availability favored enhanced algal/cyanobacterial growth. In remote Cabiúnas and Comprida Lagoons pristine conditions are preserved. Organic matter from vascular plants dominates (chain length of free lipids up to C36), which is exceptionally well preserved by acidic lagoonal waters. Differentiation between landward and seaward sites in these two lagoons is less well established due to much smaller surface/volume to catchment ratios. No anthropogenic influences are yet detectable in sediments of Cabiúnas and Comprida Lagoons.